2017
DOI: 10.1016/j.celrep.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Adenocarcinoma Therapeutic Targets Revealed by Tumor-Stroma Cross-Talk Analyses in Patient-Derived Xenografts

Abstract: SUMMARYPreclinical models based on patient-derived xenografts have remarkable specificity in distinguishing transformed human tumor cells from non-transformed murine stromal cells computationally. We obtained 29 pancreatic ductal adenocarcinoma (PDAC) xenografts from either resectable or non-resectable patients (surgery and endoscopic ultrasound-guided fine-needle aspirate, respectively). Extensive multiomic profiling revealed two subtypes with distinct clinical outcomes. These subtypes uncovered specific alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
212
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(228 citation statements)
references
References 40 publications
10
212
0
6
Order By: Relevance
“…Classical molecular biology concepts are increasingly replaced by complex multidisciplinary approaches by multinational teams that address epithelial and stromal determinants and their interplay in PDA. The importance of the dialogues between both compartments has been recently shown in an elegant PDX mouse model where molecular profiling of both the tumour cells (human origin) and the stroma (mouse origin) has enabled to establish two stroma molecular subgroups that mirror those two described at the tumour cell level 8. Based on recent precision oncology concepts in other tumour entities, several whole-genome sequencing studies and transcriptional profiling analyses have been conducted aiming at the discovery of distinct molecular subtypes in PDA that could be exploited for therapeutic stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Classical molecular biology concepts are increasingly replaced by complex multidisciplinary approaches by multinational teams that address epithelial and stromal determinants and their interplay in PDA. The importance of the dialogues between both compartments has been recently shown in an elegant PDX mouse model where molecular profiling of both the tumour cells (human origin) and the stroma (mouse origin) has enabled to establish two stroma molecular subgroups that mirror those two described at the tumour cell level 8. Based on recent precision oncology concepts in other tumour entities, several whole-genome sequencing studies and transcriptional profiling analyses have been conducted aiming at the discovery of distinct molecular subtypes in PDA that could be exploited for therapeutic stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that PDXs retain the genome-wide exomic nucleotide variants, gene copy number alterations, and DNA methylation patterns of their corresponding tumors [1][2][3][4] irrespective of the number of passages, 1,3 although clonal selection during initial engraftment and passaging of PDXs has been observed. 4 PDX models also are increasingly used in the mechanistic characterization of resistance to targeted therapies, [9][10][11] the identification of novel Cancer November 1, 2019 biomarkers 12 and therapeutic targets, 13 and the characterization of intratumoral heterogeneity. 7,8 An analysis of the treatment responses of PDXs established from 92 patients with different solid tumors demonstrated a significant association between drug response in patients and the response in mice bearing the corresponding PDXs, indicating that PDXs can predict clinical treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 An analysis of the treatment responses of PDXs established from 92 patients with different solid tumors demonstrated a significant association between drug response in patients and the response in mice bearing the corresponding PDXs, indicating that PDXs can predict clinical treatment response. 4 PDX models also are increasingly used in the mechanistic characterization of resistance to targeted therapies, [9][10][11] the identification of novel Cancer November 1, 2019 biomarkers 12 and therapeutic targets, 13 and the characterization of intratumoral heterogeneity. 14,15 Molecular characterization of lung cancer PDXs has demonstrated that these PDXs faithfully retain the genomic alterations found in their corresponding primary tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Another important point that conduct us to choose PDX as model is that it offers the posibility to distinguish between the tumor and stromal cells. In fact, sequencing profiles of a mix of human grafted cancerous and infiltrating mouse stromal cells can be analyzed separately in silico by unambiguously assigning each sequence to the human or mouse genome [6]. Therefore, we generated PDX samples for a cohort of patients (PaCaOmics) to define histological and molecular grades for each sample.…”
Section: Using Pdx To Define the Molecular Diversity Of Pdacmentioning
confidence: 99%